Regulation of oil accumulation in single glands of Eucalyptus polybractea - King, Drew James (The New phytologist, 2006)
The accumulation of terpenoid oil was examined in the leaves of Eucalyptus polybractea at scales ranging from individual oil glands to the whole plant. Variations in oil composition and concentration of oil were measured and related to both morphological and physiological parameters. Within a plant, all glands produced oil of broadly similar composition that was not regulated by leaf age or the position of the gland within the leaf. There were, however, distinct differences between plants, suggesting that composition is controlled primarily at the whole-plant level. Oil concentration, too, was regulated primarily at the whole-plant level and was limited by gland capacity. Gland capacity was linked to leaf area and thickness, the final products of leaf expansion. Leaf and plant oil composition is determined not by a mosaic of glands specializing in producing a single or a small group of compounds, but rather by glands with remarkably similar capacities for terpenoid biosynthesis, although oil concentration, limited by gland capacity, may be linked to leaf expansion rather than biosynthetic capacity